Al3+ environments in nanostructured ZnAl2O4 and their effects on the luminescence properties - da Silva, Alison A. [UNESP]; Goncalves, Agnaldo S. [UNESP]; Davolos, Marian Rosaly [UNESP]; Santagneli, Silvia H. [UNESP] (Amer Scientific Publishers, 2008)
Single-phase zinc aluminate (ZnAl(2)O(4)) with the spinel structure was successfully obtained by the Pechini method at different calcining temperatures for 4 hours. The nanoparticles are highly crystalline with no impurities related to ZnO or Al(2)O(3) residues. The microstructural environment of aluminium ions changes with heat treatment temperature, as observed by Fourier transform infrared spectroscopy. The spinel structure might present two different AlO(6) sites as evidenced by (27)Al solid-state magic-angle-spinning nuclear magnetic resonance spectra. Some AlO(4) sites were also detected for samples calcined at a temperature lower than 900 degrees C. The photoluminescence spectra show that the emission can be tuned depending on the calcining temperature. This effect was discussed on the basis of symmetry and oxygen vacancies.
Keywords: Emission Tuning; Spinel Structure; Zinc Aluminate